The epidemiology of microbial agents related to patients with multiple sclerosis (MS) - Navidinia, Masoumeh; Gholinejad, Khadijeh; Derakhshan, Safoura; Rahimipour, Ali; Kazerouni, Faranak; Sahraian, Mohammad Ali (Archives of Advances in Biosciences, 2018)
Multiple Sclerosis (MS) is one of the autoimmune diseases which affects the central nervous system and its etiology has not yet been identified. The disparity between youth and disability in reproductive ages is considered to be of particular importance for this disease and the need for research which illuminates various epidemiological, etiologic, clinical and therapeutic angles of multiple sclerosis is deeply felt. The purpose of this study is to consider the epidemiology of microbial agents related to patients with multiple sclerosis (MS). From 37 patients with multiple sclerosis according to the physician examination and McDonald criteria , serum samples were taken. Until testing, serum samples were stored in a freezer at -70 ° C. Subsequently, viral and bacterial agents were identified using specific primers and PCR method. In this study, the numbers of microbial agents were as the following: 7 retrovirus associated with MS (MRSV), 17 EBV, 8 HSV6, 11 JC virus, 10 CMV, 8 B19, 14Corona virus, 1 Helicobacter pylori, 15 Acinetobacter, 9 Borrelia burgdorferi, and 19 Chlamydia pneumonia. Identification of the relationship between different infectious agents in MS is necessary to prepare feasible data about tracing and treatment of MS related to these microorganisms that may be beneficial to clinicians to select a convenient empirical therapeutic diet in MS related to pathogens at the bedhead and can open up a new path to new therapeutic approaches.